Evolved tolerance to freshwater salinization in zooplankton: life-history trade-offs, cross-tolerance and reducing cascading effects. (21st January 2019) - Hintz, William D.; Jones, Devin K.; Relyea, Rick A.
Abstract : Recent discoveries have documented evolutionary responses to freshwater salinization. We investigated if evolutionary responses to salinization exhibit life-history trade-offs or if they can mitigate ecological impacts such as cascading effects through mechanisms of tolerance and cross-tolerance. We conducted an outdoor mesocosm experiment using populations of Daphnia pulex —a ubiquitous algal grazer—that were either naive or had previously experienced selection to become more tolerant to sodium chloride (NaCl). During the initial phase of population growth, we discovered that evolved tolerance comes at the cost of slower population growth in the absence of salt. We found evolved Daphnia populations maintained a tolerance to NaCl approximately 30 generations after the initial discovery. Evolved tolerance to NaCl also conferred cross-tolerance to a high concentration of CaCl2 (3559 µS cm −1 ) and a moderate concentration of MgCl2 (967 µS cm −1 ). A higher concentration of MgCl2 (2188 µS cm −1 ) overwhelmed the cross-tolerance and killed all Daphnia . Tolerance to NaCl did not mitigate NaCl-induced cascades leading to phytoplankton blooms, but cross-tolerance at moderate concentrations of MgCl2 and high concentrations of CaCl2 mitigated such cascading effects caused by these two salts. These discoveries highlight the important interplay between ecology and evolution in understanding the full impacts of freshwater salinization. This article is part of the theme issue 'Salt in freshwaters: causes, ecological consequences and future prospects'.